2022
DOI: 10.1001/jama.2022.1806
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Eating Disorders in Adolescents and Adults

Abstract: ImportanceEating disorders (eg, binge eating disorder, bulimia nervosa, and anorexia nervosa) are a group of psychiatric conditions defined as a disturbance in eating or eating-related behaviors that impair physical or psychosocial functioning. 1,2 The prevalence of eating disorders in the US has not been well studied; thus, current rates may underestimate the true burden of disease. According to large US cohort studies, estimated lifetime prevalences for anorexia nervosa, bulimia nervosa, and binge eating dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A recent study found that anorexia nervosa (AN) is closely related to low BMD and an increased risk of hip fracture ( 24 ). Studies have shown that the bone loss rate of the hip joint of amenorrhea women with anorexia nervosa is 2.4% per year ( 25 , 26 ). AN is a mental illness, long-term malnutrition is accompanied by severe bone loss, followed by hypogonadism and growth hormone resistance, which becomes an important intermediary factor for bone loss in patients with AN ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study found that anorexia nervosa (AN) is closely related to low BMD and an increased risk of hip fracture ( 24 ). Studies have shown that the bone loss rate of the hip joint of amenorrhea women with anorexia nervosa is 2.4% per year ( 25 , 26 ). AN is a mental illness, long-term malnutrition is accompanied by severe bone loss, followed by hypogonadism and growth hormone resistance, which becomes an important intermediary factor for bone loss in patients with AN ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, data are unavailable to support or reject this notion. Indeed, the US Preventive Services Task Force made no recommendation on universal ED screening due to a lack of research on the benefits versus harms (Davidson et al, 2022). By failing to screen all children for EDs, we miss a critical window for early intervention among those who are susceptible.…”
Section: Initial Symptom Detectionmentioning
confidence: 99%